Analisis Metode ANP pada Hubungan Kerja di PT. Pp. London Sumatera Indonesia, Tbk - Trydillah, Alrizca; Windarto, Agus Perdana; Fauzan, M (STIKOM Tunas Bangsa Pematangsiantar, 2021)
Termination of Employment (PHK) for employees is a thing that is very avoided for every employee, it stops there based on their own request, but there is also a reason for regulations that no longer allow the employee to continue his work. Cases of termination of employment (layoffs) against employees in a company often occur. In PT. PP London Sumatera Indonesia, Tbk precisely in the office of the Bah Lias Research Station (BLRS) there were 76 employees laid off. And in the Bah Lias Estate (BLE) office there were 21-22 employees who were laid off. The company will make efficiency because of the excess ratio. Standardization ratio set by the company is 0.16. But the company has exceeded the existing ratio. The service period in the company is 55 years old. After 55 years the company will retire the worker according to the applicable law (Law 13 of 2000). For employees affected by the R program from the company, their rights will be paid according to applicable laws. In this efficiency, there are 4 R program criteria, namely: lose day is workers who are often absent while working or are absent, unproductive are workers who do not have work or workers who are often sick, nearing retirement. The service period in the company is 55 years old, so it is required to retire if the work period has reached 55 years. And the last criterion is undisciplined is workers who are late for work hours and are absent from work.